2018
DOI: 10.1371/journal.pone.0204289
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of 137Cs-enriched particles to radiocesium concentrations in seafloor sediment: Reconnaissance experiment

Abstract: Autoradiography was used to detect 137Cs-enriched particles in sediment samples. The contributions of 137Cs-enriched particles to 137Cs concentrations in sediment samples ranged from 9% to 64%. These experiments revealed that the variability of 137Cs concentrations was due mainly to the heterogeneous distribution of 137Cs-enriched particles in the samples. Therefore, the heterogeneous distribution of 137Cs-enriched particles is probably one of the main factors responsible for the temporal and spatial variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Autoradiography images on the IP were scanned by a Fluor Image Analyzer (FLA-5100, Fuji Photo Film Co., Ltd.) using a 635 nm laser. The activity of the CsMPs was determined according to Ikenoue et al…”
Section: Methodsmentioning
confidence: 99%
“…Autoradiography images on the IP were scanned by a Fluor Image Analyzer (FLA-5100, Fuji Photo Film Co., Ltd.) using a 635 nm laser. The activity of the CsMPs was determined according to Ikenoue et al…”
Section: Methodsmentioning
confidence: 99%
“…The amount of these particles is relatively large, and their distribution can be approximated as locally uniform. In fact, the radioactivity concentration did not change even when the samples were measured after dividing them into five pieces of 15 g each [21]. Therefore, type A particles are not a concern in this study because it does not directly affect the results of the wide-area surveys using the towed spectrometer.…”
Section: Introductionmentioning
confidence: 91%
“…Type A has a small size (1,10 μm) with a large 134 Cs/ 137 Cs ratio (,1.04), and Type B is large (70,400 μm) with a small 134 Cs/ 137 Cs ratio (,0.93). The previous experiments suggested that type A particles are distributed widely in marine sediment, and 9,64% of cesium is composed of this type of particle [21].…”
Section: Introductionmentioning
confidence: 93%